PARENTS KNOWLEDGE AND ATTITUDE TO ORAL HYGIENE OF SPECIAL NEEDS CHILDREN - Dhiya Nabila; Renie Kumala Dewi; Galuh Dwinta Sari (Dentin, 2023)
ABSTRACTBackground: Knowledge and attitudes of parents are important in underlying the formation of children's dental and oral hygiene behavior because parents are the foundation for children's behavior and also influence children's development and independence.  The role and practice of parents can affect the dental and oral problems of special needs children which will increase when they are older. Purpose: Analyzing the relationship between parents’ knowledge and attitude toward oral hygiene of special needs children.  Material And Methods: This study uses correlational analysis with a cross-sectional approach, the sampling technique is a simple random sampling technique. The study was held at SLB Negeri Samarinda with a total sample of 52 respondents using questionnaires to parents and examine children’s oral hygiene then the data were analyzed using the Spearman rank test. Results: Parent’s knowledge of (40,4%) in the moderate level, parent’s attitudes of (75%) in the positive category, and special need children’s oral hygiene of (55,8%) in the moderate category.  The Spearman Rank test on parents’ knowledge obtained a significance of 0.000 (p<0,05) which means there is a relationship between parent knowledge toward oral hygiene of special needs children and the measurement of parent attitudes obtained a significance of 0.000 (p<0,05) which means there is a relationship between parent attitudes toward oral hygiene of special needs children Conclusion: The higher of knowledge and attitudes of parents toward oral hygiene, the better oral hygiene of special need children will.Keywords: Oral hygiene of special needs children, parent attitude, parent knowledge